Enhanced Fixed Point Theorems for Compatible and Semi Compatible Mappings of Type α and β In Menger Spaces - Keer, Pradip Kumar; Agrawal, Geeta (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
This paper presents advanced fixed-point theorems for both compatible and semi-compatible mappings of types α and β within Menger spaces. We extend classical results by exploring the conditions under which these mappings exhibit enhanced fixed-point properties. Our findings include new theorems with detailed proofs, contributing to a deeper understanding of the interplay between compatibility conditions and fixed-point existence. These results have potential applications in various mathematical and applied fields.